Determinants of Duration of Leakage in Women with a Fistula Diagnosis: A Prospective Cohort Study in East African Countries (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2022)
Introduction: Women living with Vesico Vaginal Fistula (VVF) continue to suffer for many years, and  often in silence. Around the world, over 2 million women live with a fistula and new cases continue to be  reported especially in low income countries. These countries also tend to have a high maternal morbidity and  mortality rates.  Objectives: To establish the duration of leakage in a cohort of women diagnosed with fistula.  Methodology: A prospective cohort study conducted over a three-year period. Patients with confirmed  diagnosis of VVF and or Recto Vaginal fistula (RVF) were eligible for study. A structured questionnaire was  used to collect information on sociodemographic profiles, presenting symptoms and duration of leakage.  Results: A total of one thousand and twenty-four patients were enrolled in the study, 34% had lived with the  fistula for more than 3 years. The majority (70%) were young, with a mean age of 20. Literacy levels were  low in this cohort. Urban women were more likely to access fistula care services compared to their rural  counterparts (p>0.0001).  Conclusion: Individual and country level factors influenced the duration women lived with fistula before  surgical repair.